Rede de arborização urbana : conflitos e interfaces com as outras redes de infraestrutura - Bresolin, Raquel Rhodem (2009)
The study approached urban arborization, analyzing the conflicts regarding the other infrastructure nets according to their location in the urban space, in three levels subsoil, terrestrial and aerial in a medium-sized city, Passo Fundo RS. The city plays a leading role due to its regional and local importance in terms of economy, education and culture. The analysis was carried out through a case study in two districts of the city with different urbanistic characteristics, and the chosing criterion used was a high urban density neighborhood and a low urban density one. Technical aspects were observed through bibliographic revision and existing normatization, and the methodology used was the Post-Occupancy Evaluation. The objective was to verify users satisfaction in regard to urban arborization and infrastructure existing nets. From data collected in loco in the study areas, appellant conflicts between arborization and infrastructure nets in two areas studied were registered in aerial, terrestrial levels, as well as possible conflicts in subsoil ones. The most incident conflict verified in both areas is in aerial level while the most significant one is in soil level with the presence of superficial roots that bring discomfort and threat to pedestrian Moreover, the urban law on arborization currently in force is not applied. The results and recommendations are presented according to their localization in the urban space and are medium and long-term interventions to the areas studied. The research aimed to determine criteria for implementation of urban arborization and provide recommendations that can subsidize knowledge for future interventions in the urban space of Passo Fundo, as well as in other municipalities